Answer:
32
Step-by-step explanation: OH NO MY SEXUALITY ITS BROCKEN
∑ Hey, jillianwagler ⊃
Answer:
![\left(2x-1\right)\left(2x+5\right)](https://tex.z-dn.net/?f=%5Cleft%282x-1%5Cright%29%5Cleft%282x%2B5%5Cright%29)
Step-by-step explanation:
<u><em>║Given info║:</em></u>
<em>Factor completely: </em>![4x^2 +8x -5](https://tex.z-dn.net/?f=4x%5E2%20%2B8x%20-5)
<u><em>Solution~:</em></u>
<em>Breaking the expression~: </em>![\left(4x^2-2x\right)+\left(10x-5\right)](https://tex.z-dn.net/?f=%5Cleft%284x%5E2-2x%5Cright%29%2B%5Cleft%2810x-5%5Cright%29)
<em>Factor out 2x from 4x² -2x : 2x(2x-1)</em>
<em>Factor out 5 from 10x - 5 : 5(2x - 1)</em>
<em>Put together: </em>![=2x\left(2x-1\right)+5\left(2x-1\right)](https://tex.z-dn.net/?f=%3D2x%5Cleft%282x-1%5Cright%29%2B5%5Cleft%282x-1%5Cright%29)
Factor out 2x - 1: ![=\left(2x-1\right)\left(2x+5\right)](https://tex.z-dn.net/?f=%3D%5Cleft%282x-1%5Cright%29%5Cleft%282x%2B5%5Cright%29)
<u><em>xcookiex12</em></u>
<em>8/19/2022</em>
Answer:
c = -a - b + 180
Step-by-step explanation:
Isolate the c. Note the equal sign, what you do to one side, you do to the other. Subtract a and b from both sides
a (-a) + b (-b) + c = 180 (-a) (-b)
c = 180 - a - b
c = -a - b + 180 is your answer
~
I'll assume the above equation is: 9 - 7x = 7 - 4(2x+3)
* do distributive multiplication
9 - 7x = 7 - 8x - 12
*move like terms
-7x + 8x = 7 - 12 - 9
* solve for x
x = 7 - 21
x = -14
To check, substitute x by its value -14
9 - 7x = 7 - 4(2x+3)
9 - 7(-14) = 7 -4[2(-14) + 3]
9 + 98 = 7 - 4(-28 +3)
107 = 7 - 4(-25)
107 = 7 + 100
107 = 107